Broadband Enhancement of Mid‐Wave Infrared Absorption in a Multi‐Resonant Nanocrystal‐Based Device. Issue 9 (27th March 2022) - Dang, Tung Huu; Abadie, Claire; Khalili, Adrien; Gréboval, Charlie; Zhang, Huichen; Prado, Yoann; Xu, Xiang Zhen; Gacemi, Djamal; Descamps‐Mandine, Armel; Ithurria, Sandrine; Todorov, Yanko; Sirtori, Carlo; et al.
Abstract: Light management is one of the main challenges to address when designing a sensor from a nanocrystal (NC) array. Indeed, the carrier diffusion length, limited by hopping mechanism, is much shorter than the absorption depth. Several types of resonators (plasmon, Bragg mirror, guided mode, Fabry–Perot cavity) have been proposed to reduce the volume where light is absorbed. All of them are inherently narrow bands, while imaging applications focus on broadband sensing. Here, an infrared sensor in the short and mid‐wave infrared (SWIR and MWIR) that combines three different photonic modes is proposed to achieve broadband enhancement of the light absorption. Moreover, it is shown that these three modes can be obtained from a simple structure where the NC film is coupled only to a grating and a top metallic layer. The obtained device achieves a high responsivity of >700 mA W –1, a detectivity up to 2 × 10 10  Jones at 80 K, and a short response time of 11 µs. Abstract : This work presents a strategy to enhance the light absorption in a HgTe nanocrystal film used for light detection in which multiple light resonances are designed to achieve a broadband strong absorption.